Business Competence Formation Model in Company Based On Supply Chain Management - Anastasiia F. Iudintseva; Evgeniya V.Gutman; Valeria Sh.Maslennikova; Ilseyar I.Iskhakova; Anastasia V.Fakhrutdinova (International Journal of Supply Chain Management, 2020)
Abstract— The article considers the problem of developing a cognitive model for the business competence formation based on supply chain management in the company. The model includes the following components: purpose, methodological approaches and principles, content, pedagogical conditions, business competence criteria and indicators. The model subject component is presented by customer as full-fledged participants of the educational process and is characterized by their dynamic unity aimed at creating subject-subject educational relationship. The pedagogical activity model in an educational organization is a single process of interaction and cooperation between company and customer, joint creative activities to form social and professional competencies contributing to the complex professional problems resolution and spiritual and moral upbringing. The purpose of the model implementation is to develop the student’s personality, intellectual, emotional-volitional, communicative skills and other personal qualities such as purposefulness, responsibility, humanity, tolerance, citizenship, etc. The tasks of creating business competence are to develop their professional orientation; readiness for non-standard, creative, incl. professional solutions; self-organization skills; flexibility regarding new requirements; determination in preparation for the performance of their civic duties, familiarization with legal norms in force in society.